Finding Funding for Executive Education and Research: Ten Key Principles - Wardale, Dorothy; Lord, Linley (ANZAM, 2012)
There is increasing pressure on universities in Australia, as elsewhere, to seek alternative funding sources. There is also a growing expectation that academic staff will be actively involved in the revenue raising process. This paper looks specifically at two areas of activity, contract research and executive education and discusses ten principles we have found useful in generating funding for these activities. In examining our practice we draw on social capital theory, and in particular relational social capital to illustrate how the principles we have identified are embedded in theory. We conclude with recommendations particularly for early career academics building their careers who wish to leverage from such funding opportunities.